Author Correction: Antibiotic susceptibility signatures identify potential antimicrobial targets in the Acinetobacter baumannii cell envelope - Edward Geisinger (Nature Portfolio, 2020)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-020-20098-z